Dendritic Cells: A Spot on Sialic Acid - Crespo, Hélio J.; Lau, Joseph T.; Videira, Paula A. (Frontiers in Immunology, 2013)
Glycans decorating cell surface and secreted proteins and lipids occupy the juncture where critical host-host and host-pathogen interactions occur. The role of glycan epitopes in cell-cell and cell-pathogen adhesive events is already well-established, and cell surface glycan structures change rapidly in response to stimulus and inflammatory cues. Despite the wide acceptance that glycans are centrally implicated in immunity, exactly how glycan changes contribute to the overall immune response remains poorly defined. The terminal position of the glycan chains are usually occupied by sialic acids. And sialic acid-modified structures form the key fundamental determinants for a number of receptors with known involvement in cellular adhesiveness and cell trafficking, such as the Selectins and the Siglec families of carbohydrate recognizing receptors. On dendritic cells (DC), sialic acid-modified structures are involved in all their functions and their expression changes along differentiation and activation with important functional implications. DCs preside over the transition from innate to the adaptive immune repertoires, and no other cell has the relevance of role in antigen screening, uptake and presentation to ultimately trigger the adaptive immune response. This review focuses on the developmental regulation of DC surface sialic acids and how manipulation of DC surface sialic acids can affect immune-critical DC functions by altering antigen endocytosis, pathogen and tumor cell recognition, cell recruitment, and capacity for T cell priming. The existing evidence points to a potential of DC surface sialylation as a therapeutic target to improve and diversify DC-based therapies.